Positive processes of change among male and female clients treated for alcohol and/or drug problems. (March 2017) - von Greiff, Ninive; Skogens, Lisa
Summary: In social work practice, the role of substance use is often encountered in the context of other social problems such as child abuse and domestic violence. This article compares descriptions of important factors for initiating and maintaining positive changes among male and female clients treated for alcohol and/or drug problems. The results have a bearing both on substance use treatment and on other areas in social work practice where these problems are encountered. Studies highlighting gender perspective indicate differences regarding experience of alcohol and drug problems and treatment. An advantage of the study is the qualitative analysis of a rather comprehensive material ( n  = 90) enabling more general conclusions than in previous research with a limited number of clients. Findings: Women more often than men stress poor mental health and their children as important for initiating change. When referring to partners, women report abusive rather than supportive partners while the opposite applies to men. For maintaining change, male clients more often stress changes in ways of thinking and feeling as important. Men also report becoming more sensitive while women get more active. This can be understood as transcending of gender with possibilities of a broader repertoire of how to act. Applications: A challenge for practical treatment work is to create possibilities for clients to broaden their repertoire of ways of living and thinking about themselves, expressed by women as the importance of taking space and speaking up and by the men of showing emotion and listening more.